Pertumbuhan Ekonomi Dan Pengangguran Terhadap Kemiskinan Di Jawa Timur - AMEILIA KARISMA (Jurnal Pendidikan Ekonomi (JUPE), 2013)
Poverty can be identified with the level of prosperity of a society, be it in rural or urban areas. Although Indonesia's East Java in the first rank economic growth in 2011, however, ranks third in East Java poverty level. In certain years, despite increased economic growth and poverty but the unemployment rate also increased. This study uses secondary data obtained from the central statistical agency and through the internet to complete the data. The analysis method used in this study is a multiple linear regression with the help of Eviews software. The results showed that the variables of economic growth and unemployment have a significant impact on poverty through the variable t test results with the results of the economic growth variable has a probability of 0.0011 and a variable rate of open unemployment has a probability of 0.0006. The coefficient of determination (R2) of 0863, this means that the variation of 86.3 percent poverty in East Java can be explained by variations in two independent variables namely economic growth and unemployment. While the remaining 13.7 percent is explained by other variables not mentioned in the research model Keywords: poverty, economic growth, unemployment rate.